2020
DOI: 10.1007/s00330-020-07270-1
|View full text |Cite
|
Sign up to set email alerts
|

Chest X-ray for predicting mortality and the need for ventilatory support in COVID-19 patients presenting to the emergency department

Abstract: Objectives To evaluate the inter-rater agreement of chest X-ray (CXR) findings in coronavirus disease 2019 (COVID-19) and to determine the value of initial CXR along with demographic, clinical, and laboratory data at emergency department (ED) presentation for predicting mortality and the need for ventilatory support. Methods A total of 340 COVID-19 patients who underwent CXR in the ED setting (March 1–13, 2020) were retrospectively included. Two reviewers independently assessed CXR abnormalities, including g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
145
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(158 citation statements)
references
References 26 publications
10
145
2
1
Order By: Relevance
“…Mortality in other Italian hospitals in northern Italy varied between 43.6% ( 74 ) and 23.2% ( 75 ). In other hospitals in the Lombardy area, mortality ranged from 14.4 to 36.7% ( 75 80 ). Including our data, during the first epidemic wave the overall average in-hospital mortality in Italy therefore ranged around 30%.…”
Section: Shadows Lights and Lessons From Covidmentioning
confidence: 99%
“…Mortality in other Italian hospitals in northern Italy varied between 43.6% ( 74 ) and 23.2% ( 75 ). In other hospitals in the Lombardy area, mortality ranged from 14.4 to 36.7% ( 75 80 ). Including our data, during the first epidemic wave the overall average in-hospital mortality in Italy therefore ranged around 30%.…”
Section: Shadows Lights and Lessons From Covidmentioning
confidence: 99%
“…Moreover the American College of Radiology and Society of Thoracic Radiology in the United States cautioned against their widespread use for assessment and monitoring disease course (18). However several studies in Asia, Europe and United States have indicated that chest radiographs and CT may have a role in the prediction of clinical evolution including need of ICU admission (19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…A total of thirteen studies 1 6 , 8 , 9 , 10 , 11 , 12 , 13 14 reporting 58,183 laboratory-confirmed COVID-19 patients were included. The main characteristics of the selected studies are demonstrated in Table 1 .…”
mentioning
confidence: 99%